2004
DOI: 10.1081/ncn-200034057
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, In Vitro Anticancer Evaluation, and Interference with Cell Cycle Progression of N‐Phosphoamino Acid Esters of Zidovudine and Stavudine

Abstract: A series of N-diisopropylphosphoryl (DIPP) L-amino acid ester prodrugs of zidovudine (AZT) (3a-3e) and stavudine (d4T) (4a-4e) has been prepared. The activity of these compounds against MCF-7 cells (human pleural effusion breast adenocarcinoma cell line) and K562 cells (human chronic myeloid leukemia (CML) cell line) was evaluated. In difference from that of AZT amino acid phosphoramidates, the alophatic amino acid esters of AZT were found to be more cytotoxic than the aromatic analogues toward MCF-7 cell. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
3
7
0
Order By: Relevance
“…Cell cycle abnormalities induced by AZT have been previously observed in human HL60 (Roskrow & Wickramasinghe, 1990), Jurkat (Wu et al, 2004), Hela (Olivero et al, 2005) and lymphoblastoid cells (Olivero et al, 2010). Our results showed that the combination of AZT and emodin caused an accumulation of K562/ADM cells in S phase, which is consistent with Oliver's findings (Olivero et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…Cell cycle abnormalities induced by AZT have been previously observed in human HL60 (Roskrow & Wickramasinghe, 1990), Jurkat (Wu et al, 2004), Hela (Olivero et al, 2005) and lymphoblastoid cells (Olivero et al, 2010). Our results showed that the combination of AZT and emodin caused an accumulation of K562/ADM cells in S phase, which is consistent with Oliver's findings (Olivero et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…The resulting damaged DNA might either delay cell cycle progression until the damage is repaired or cause apoptotic cell death (Melana et al 1998; Falchetti et al 2005; Humer et al 2008; Fang and Beland 2009; Fang et al 2009b). In addition, recent studies have demonstrated that XPC, via the nucleotide excision repair pathway, is essential for the repair of AZT-induced DNA damage in human HepG2 cells and THLE2 cells (Wu et al 2011, 2013) In the current study, molecular and cellular function pathway analysis indicated that most of the 253 common genes altered in the same direction by AZT at the equi-toxic concentrations in both HepG2 cells and THLE2 cells were involved in cell death and survival, cellular growth and proliferation, cell cycle, and DNA replication, recombination, and repair (Table 2), which is in consistent with previous studies (Fang and Beland 2009; Collier et al 2003; Wu et al 2004; Melana et al 1998; Roskrow and Wickramasinghe 1990; Falchetti et al 2005; Humer et al 2008). …”
Section: Discussionsupporting
confidence: 91%
“…The differential sensitivity of cancer cells to AZT has been related to a combination of effects, including a delay of cell cycle progression, the induction of apoptosis, and a decrease in telomerase activity (Melana et al 1998; Collier et al 2003; Wu et al 2004; Falchetti et al 2005; Humer et al 2008; Fang and Beland 2009). Cancer cells also have higher growth rates than normal cells, with a concomitant higher rate of thymidine turnover, which could contribute to their increased sensitivity to AZT (Melana et al 1998; Humer et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Cell cycle abnormalities induced by AZT have been previously reported in human HeLa (Olivero et al , 2005), HL60 (Roskrow and Wickramasinghe, 1990), and Jurkat cells (Wu et al , 2004). Prior studies performed in our laboratory, using HeLa cells, revealed a delay in the cell cycle, with a dose-related significant increase in percentage of S-phase cell accumulation after 24 h of exposure to 63–500μM AZT.…”
Section: Discussionmentioning
confidence: 87%